PENGARUH PARTISIPASI DALAM BELAJAR KELOMPOK TERHADAP HASIL BELAJAR SISWA SMA SANTO FRANSISKUS ASISI PONTIANAK - Wilhelmus, Aloysius Petrus; Budjang, Gusti; Supriyadi, Supriyadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of the study was "The Influence of Participation in Group Learning of Student Results on Sociology Subjects". The problem of research is how the influence of participation in group learning on student learning outcomes. The purpose of the study was to know the participation of students in group learning to improve learning outcomes. The method used is quantitative method. The results of this study are (1) Student participation in learning sociology lessons group included in high category that is as much as 74%. (2) As many as 45% of the students' learning outcomes are included in the very high category, and 50% of the respondents are included in the high category. (3) There is influence of participation in group learning on student learning outcomes. Constant value is 85,334, if participation in study group (X) is 0 (zero), then learning result (Y) is 85,334. The value of regression coefficient of variable participation in learning group (X) is 0.79. This means that every increase in participation in group study (X) is 1, then the learning outcome (Y) will increase by 0.79. (4) The amount of influence of variable X to variable Y (Coefficient of Determination) of 26%.Â Keywords : Participation, Group Learning, Learning Outcomes